Análise das respostas sensoriais aos alimentos por meio do teste de amplitude - Paes Chaves , José Benício; Teixeira Coelho , Dilson; Pereira , Alonso Salustiano; Lima Martyn , Maria Elilce (Revista Ceres, 2025)
The objective was to compare statistical methods of analysis for sensorial data. The Range method, the analysis of variance, and Tukey’s test were used in these comparisons.